2016
DOI: 10.1016/j.ebiom.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 , DNMT3A and DNMT3B Polymorphisms Associated With Gastric Cancer Risk: A Systematic Review and Meta-analysis

Abstract: BackgroundIncreasing studies showed that abnormal changes in single nucleotide polymorphisms (SNPs) of DNMTs (DNMT1, DNMT3A and DNMT3B) were associated with occurrence or decrease of various tumors. However, the associations between DNMTs variations and gastric cancer (GC) risk were still conflicting. We aimed to assess the effect of DNMTs polymorphisms on the susceptibility to GC.MethodsFirstly, we did a meta-analysis for 7 SNPs (rs16999593, rs2228611, rs8101866 in DNMT1, rs1550117, rs13420827 in DNMT3A, rs15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 43 publications
1
40
0
2
Order By: Relevance
“…Although its functionality has not been completely elucidated, three possible mechanisms have been suggested that might affect gene expression, including altered splicing, linkage disequilibrium with other functional polymorphisms and alteration of transcription factor binding affinity . Nevertheless, the DNMT3B rs1569686 polymorphism has been investigated in numerous studies as a potential risk factor for different diseases, including cancer, autoimmune conditions, fertility disorders and pregnancy complications . Although this polymorphism has not been investigated previously in RSA, maternal GG genotype and G allele were detected as risk genotypes for Down syndrome, which is similar to our results .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although its functionality has not been completely elucidated, three possible mechanisms have been suggested that might affect gene expression, including altered splicing, linkage disequilibrium with other functional polymorphisms and alteration of transcription factor binding affinity . Nevertheless, the DNMT3B rs1569686 polymorphism has been investigated in numerous studies as a potential risk factor for different diseases, including cancer, autoimmune conditions, fertility disorders and pregnancy complications . Although this polymorphism has not been investigated previously in RSA, maternal GG genotype and G allele were detected as risk genotypes for Down syndrome, which is similar to our results .…”
Section: Discussionsupporting
confidence: 87%
“…In another study, maternal DNMT3B rs1569686‐rs2424913G‐T haplotype also increased the odds for Down syndrome . In contrast to these results, in other diseases, for instance cancer and schizophrenia, the DNMT3B rs1569686 G allele is the protective allele …”
Section: Discussionmentioning
confidence: 89%
“…In addition, 23.5% allelic loss of DNMT3A was observed in GC (70). Increment of functional polymorphism of DNMT1, DNMT3A and DNMT3B were found in gastric neoplasm and have been found to be associated with development and progression of GC (65,(71)(72)(73). One meta-analysis showed that DNMT1 rs16999593 and DNMT3A rs1550117 could result in GC and that DNMT3B rs1569686 may be a protective factor against gastric carcinogenesis (73).…”
Section: Dna Methylation In Gcmentioning
confidence: 99%
“…Inhibition of DNMT1 and HDAC either by knockdown or by pharmaceutical agents in this setting restored the sensitivity of cisplatin. Although it is generally recognized as maintenance apparatus for cellular epigenomic landscape, dysregulated expression or activity of DNMT1 is frequently associated with malignancy transformation . However, the potential link between DNMT1 with drug resistance in ovarian cancer has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%